Numerical and Experimental Analysis of EffectorsUsed in Active Protection Systems - Robert PANOWICZ (Numeryczno-eksperymentalne analizy efektorów stosowanych w systemach obrony aktywnej, 2016)
The paper presents numerical and experimental analyses of effectors used in active protection systems. In the numerical analyses, the ALE method was used with FSI. Two types of destructors were analysed. The first destructor is a rectangular directed fragmentation warhead which can be mounted on the protected object. The second one is cylindrical and is a component of an antimissile. In both types of destructors we can distinguish several main parts, such as: the case, explosive material and fragmentation liner. The fragmentation liner is built from resin with submerged metallic spheres or cylinders. The fragmentation liner forms a cloud of fragments when the explosive material, located in direct contact with the liner, explodes. In order to perform numerical analyses, three-dimensional models of the destructors were designed in the HyperMesh software. The numerical analyses were performed with the Ls-Dyna software. The results of experimental tests carried out on one of the destructors are also presented in the study.
Keywords: Analiza efektorów dla systemów obrony